1650 . .. :


.
,
.
,
?

" ", "" " ". .
18.03.2013

LiveJournal Vkontakte Facebook Twitter

1...2 

Cx + 1x - 2 + 2Cx - 13 = 7(x - 1).

______________________________________

, :

(x + 1)!

(x - 2)!3!

+ 2(x - 1)!

(x - 4)!3!

= 7(x - 1);

, 3!,

(x + 1)x(x - 1) + 2(x - 1)(x - 2)(x - 3) = 3!7(x - 1)

(x + 1)x + 2(x - 2)(x - 3) = 42

x2 + x + 2x2 - 10x + 12 = 42

x2 - 3x - 10 = 0

, : x = -2, x = 5. x , x = 5.

: x = 5.


Ax3 - 2Cx4 = 3Ax2.

__________________________________

, :

x!

(x - 3)!

- 2 x!

(x - 4)!4!

= 3 x!

(x - 2)!

12:

12x(x - 1)(x - 2) - x(x - 1)(x - 2)(x - 3) = 36x(x - 1)

12(x - 2) - (x - 2)(x - 3) = 36

12x - 24 - x2 + 5x - 6 - 36 = 0

x2 - 17x + 66 = 0

: x1 = 11, x2 = 6.

: x = 11 x = 6.


Axx - 3 = xPx - 2.

____________________________

, :

x!

3!

= x(x - 2)!

x(x - 1)(x - 2)! = 6x(x - 2)!

x - 1 = 6

x = 7

: x = 7.


Pn = (n - 1)(Pn - 1 + Pn - 2).

____________________________________

, :

n! = (n - 1)((n - 1)! + (n - 2)!)

n - 1:

n(n - 2)! = ((n - 1)((n - 2)! + (n - 2)!)

n(n - 2)! = (n - 2)!(n - 1 + 1)

n(n - 2)! = n(n - 2)!

0 = 0.

.


1...2 
2009-2012 . " - !" - , . .
Rambler's Top100